Metodologia para avaliação da eficiência do indicador de DEC Programado no sistema de distribuição de energia elétrica - Saldanha, Taric Magalhães (Universidade do Vale do Rio dos Sinos, 2023)
The economic, social, and sustainable development of any region in the world relies on having sufficient and reliable energy at an appropriate price for the local reality. In this context, the distribution of electric power plays a key role and should ensure fair prices, service quality, and the quality of the supplied energy. In this regard, service provision can be evaluated through the analysis of indicators that demonstrate the evolution of the results themselves, the comparison with established regulatory targets or benchmarks, or even the comparative mode with companies in the same production sector, region, size, or other specific characteristic that is desired to be compared. For the electric power distribution model, in which regulatory bodies establish increasingly higher quality standards each year, investment in network improvement is crucial to be carried out with greater efficiency. In other words, the works must be the best possible and their execution should cause minimal impact on technical indicators and customer perception. In a scenario of constant need for investments in the distribution network, the optimization of the scheduled interruption component becomes a fundamental factor in determining the maximum investment with the lowest impact, so that the overall indicator perceived by the customer follows a downward trajectory over time. This study develops a methodology for analyzing and defining the attributes that each electric power distribution system has specifically and how each business unit is impacted by local characteristics in relation to the efficiency of the Planned Energy Interruption Duration (DEC Programmed) indicator during the process of executing works for system improvement, expansion, and maintenance. The application and utilization of a consistent database allow the model to provide reliability in its application and usage. Thus, the work proposes an evaluation methodology and the construction of a performance ranking that can be used in other electric power distribution companies, contributing to new studies and assessments of the efficiency of each company while respecting their specific characteristics and attributes of each operation.
Keywords: DEC Programado; Indicador; Eficiência; Planejamento de rede de distribuição; Distribuição de energia elétrica; Investimento; Programed SAIDI; Indicator; Efficiency; Distribution network planning; Electrical power distribution; Investment; ACCNPQ::Engenharias::Engenharia Elétrica